The Where, When, How, and Why of Hyaluronan Binding by Immune Cells - Lee-Sayer, Sally S. M.; Dong, Yifei; Arif, Arif A.; Olsson, Mia; Brown, Kelly L.; Johnson, Pauline (Frontiers in Immunology, 2015)
Hyaluronan is made and extruded from cells to form a pericellular or extracellular matrix (ECM) and is present in virtually all tissues in the body. The size and form of hyaluronan present in tissues is indicative of a healthy or inflamed tissue, and the interactions of hyaluronan with immune cells can influence their response. Thus in order to understand how inflammation is regulated, it is necessary to understand these interactions and their consequences. Although there is a large turnover of hyaluronan in our bodies, the large molecular mass form of hyaluronan predominates in healthy tissues. Upon tissue damage and/or infection, the ECM and hyaluronan are broken down and an inflammatory response ensues. As inflammation is resolved, the ECM is restored and high molecular mass hyaluronan predominates again. Immune cells encounter hyaluronan in the tissues and lymphoid organs and respond differently to high and low molecular mass forms. Immune cells differ in their ability to bind hyaluronan and this can vary with the cell type and their activation state. For example, peritoneal macrophages do not bind soluble hyaluronan but can be induced to bind after exposure to inflammatory stimuli. Likewise, naïve T cells, which typically express low levels of CD44, the hyaluronan receptor, do not bind hyaluronan until they undergo antigen-stimulated T cell proliferation and upregulate CD44. Despite substantial knowledge of where and when immune cells bind hyaluronan, why immune cells bind hyaluronan remains a major outstanding question. Here, we review what is currently known about the interactions of hyaluronan with immune cells in both healthy and inflamed tissues and discuss how hyaluronan binding by immune cells influences the inflammatory response.